The perception of fairness of staff selection procedure and its influence on anxiety among successful candidates - Noorfatinah, Fauzi (2016)
The purpose of this research was to evaluate the staff perception of fairness of the selection procedure in University Malaysia Pahang (UMP), and it is also to examine how the perception of fairness of UMP selection procedures may affect staff anxiety. Besides that, this research will answer that state in the research questions. There are several problems about this research and it is stated in 1.3 which is the problem statement have been discussed. Moreover, this research also has the various process that has been discussed in 3.4 which is research process. The method used in this research is quantitative method which is by using a questionnaire. The questionnaire or survey form consists of three parts including parts A which is about demography questionnaires, parts B about anxiety rating scale and it is all about staff anxiety, and part C is about perception of fairness of the selection procedure. Respondents that involved in this research are from several departments and position in the UMP. All respondents were selected randomly based on several positions such as administrative officer and vocational training officers. The results of this research will provide information on how to manage the selection procedure in order to achieve fairness in the selection procedure.